The Scientific Image of Ferdinand Verbiest and the Jesuits in China (The Macau Ricci Institute Journal, 2023)
Ferdinand Verbiest is a representative figure among the Jesuits who came to China during the Ming and Qing dynasties. The common view of later generations is to place him alongside his predecessors Matteo Ricci and Johann Adam Schall von Bell, shaping them as leaders of Western Learning Spreading to the East and disseminators of Western science.However, the scientific image of Verbiest and the Jesuits in China has not always been like this, and it can be examined according to the general division of Chinese history into three stages: Ming and Qing dynasties, modern times, and contemporary times. The significance of Verbiest will also be discussed from the history of evaluation to the evaluation of history.Keywords: Ferdinand Verbiest, the Jesuits, scientific image, science